Public communication and outreach by mosquito programs in the United States. - Nicole Thomas; Jo Anne G Balanay; Sachiyo Shearman; Stephanie L Richards (PLOS Global Public Health)
Blood feeding female mosquitoes cause itchy welts and can transmit pathogens that cause diseases such as chikungunya, malaria, West Nile encephalitis, and Zika. Mosquito control programs conduct mosquito, pathogen, and epidemiological surveillance, carry out source reduction, treat mosquito habitats with larvicides or adulticides, and disseminate information to the public. Here, 100 organizations (e.g., private/public mosquito control programs, national professional mosquito/pest control associations) in the United States were asked to complete a survey (N = 39 respondents) about their public communication and outreach efforts. Results indicate most programs (N = 27, 69%) have dedicated personnel for public communication. A checklist was constructed to compare communication strategies between a subset of program websites and Facebook pages. Recommendations for improving public communication and outreach strategies (e.g., digital tools, more frequent updates, public engagement strategies) for mosquito control programs are discussed.